PENERAPAN INTERNET SEHAT SEBAGAI INTERNET SERVICE PROVIDER MENGGUNAKAN NETWORK MONITORING SYSTEM ZABBIX DAN SQUID PROXY - Saleh Dwiyatno; Edy Rakhmat; Sulistiyono Sulistiyono; M Rafi Mahruzzaman (LPPM Unbaja, 2021)
Internet users continue to grow. However, there are still many who have not experienced the Internet. One of the contributing factors is the cost of the Internet which is not cheap. Most Internet users get Internet access by subscribing to their respective ISPs. In addition, today more and more crimes are committed via the Internet. This study aims to provide a solution to reduce the cost of subscribing to an ISP and provide healthy Internet access. At Ciruas Center Shops, all traders and buyers use the Internet. Even if it's just for entertainment or even for buying and selling. The system applied in this research is where Internet users can get Internet access only by subscribing to one ISP. That way the fees paid to the ISP can be paid by mutual cooperation. The result of this research is an Internet provider system in which there is Zabbix Network Monitoring System (NMS) software as a network traffic monitor and Squid Proxy as a barrier as well as security when connected to the Internet.